Tat-HSP22 inhibits oxidative stress-induced hippocampal neuronal cell death by regulation of the mitochondrial pathway. Issue 1 (December 2017) - Jo, Hyo; Kim, Dae; Shin, Min; Cho, Su; Park, Jung; Lee, Chi; Yeo, Eun; Choi, Yeon; Yeo, Hyeon; Sohn, Eun; Son, Ora; Cho, Sung-Woo; et al.
Abstract Oxidative stress plays an important role in the progression of various neuronal diseases including ischemia. Heat shock protein 22 (HSP22) is known to protect cells against oxidative stress. However, the protective effects and mechanisms of HSP22 in hippocampal neuronal cells under oxidative stress remain unknown. In this study, we determined whether HSP22 protects against hydrogen peroxide (H2 O2 )-induced oxidative stress in HT-22 using Tat-HSP22 fusion protein. We found that Tat-HSP22 transduced into HT-22 cells and that H2 O2 -induced cell death, oxidative stress, and DNA damage were significantly reduced by Tat-HSP22. In addition, Tat-HSP22 markedly inhibited H2 O2 -induced mitochondrial membrane potential, cytochromec release, cleaved caspase-3, and Bax expression levels, while Bcl-2 expression levels were increased in HT-22 cells. Further, we showed that Tat-HSP22 transduced into animal brain and inhibited cleaved-caspase-3 expression levels as well as significantly inhibited hippocampal neuronal cell death in the CA1 region of animals in the ischemic animal model. In the present study, we demonstrated that transduced Tat-HSP22 attenuates oxidative stress-induced hippocampal neuronal cell death through the mitochondrial signaling pathway and plays a crucial role in inhibiting neuronal cell death, suggesting that Tat-HSP22 protein may be used to prevent oxidative stress-related brain diseases including ischemia.